Efecto de la epoca de siembra y edad de cosecha en el rendimiento de yuca - Castro Merino, A. (International Center for Tropical Agriculture, 1980)
A trial was conducted on planting date and age at harvest at 2 exptl stations of the Instituto Colombiano Agropecuario -Carimagua (Meta) and Caribia (Magdalena)- to evaluate the physical production and quality of cassava produced under different climatic conditions and to identify a continuous production system for cassava. Six planting dates (every 2 mo throughout the yr) were evaluated at each locality, with monthly harvests from 7-12 mo of age. A split plot design with 4 replications was used. In both regions, early planting dates produced yields significantly superior to those of late plantings. In relation to the age at harvesting, greater than productivity was obtained at both localities when the crop was 10- 12 mo old. Optimum planting time for max root production extends over a 3-4 mo period at the beginning of the rainy season. Starch content is relatively constant over time. Transition periods from drought to rainfall reduce starch content in the roots. (CIAT)